SANS investigations of CO2 adsorption in microporous carbon. (December 2015) - Bahadur, J.; Melnichenko, Y.B.; He, L.; Contescu, C.I.; Gallego, N.C.; Carmichael, J.R.
Abstract: The high pressure adsorption behavior of CO2 at T = 296 K in microporous carbon was investigated by small-angle neutron scattering (SANS) technique. A strong densification of CO2 in micropores accompanied by non-monotonic adsorption-induced pore deformation was observed. The density of confined CO2 increases rapidly with pressure and reaches the liquid –like density at 20 bar, which corresponds to the relative pressure of P/Psat ∼0.3. At P > 20 bar density of confined CO2 increases slowly approaching a plateau at higher pressure. The size of micropores first increases with pressure, reaches a maximum at 20 bar, and then decreases with pressure. A complementary SANS experiment conducted on the same microporous carbon saturated with neutron-transparent and non-adsorbing inert gas argon shows no deformation of micropores at pressures up to ∼200 bars. This result demonstrates that the observed deformation of micropores in CO2 is an adsorption-induced phenomenon, caused by the solvation pressure - induced strain and strong densification of confined CO2.